2021
DOI: 10.3390/su13031476
|View full text |Cite
|
Sign up to set email alerts
|

Linking Critical Thinking and Knowledge Management: A Conceptual Analysis

Abstract: Knowledge management and critical thinking are two broad and important phenomena for contemporary society. Their concepts are both well-discussed in the literature. However, the existing conceptual links between them have not been analyzed, and the role of critical thinking in the process of effective knowledge management has not been revealed. This article aims to fill this gap by presenting the conceptual connections between knowledge management and critical thinking. In order to reveal the inner structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 100 publications
2
7
0
Order By: Relevance
“…According to the employees, critical thinking is also strongly expressed in the context of information and knowledge management. This is in line with the results of a previous study (Indrašienė et al, 2021) emphasising that critical thinking can be interpreted in three ways: (1) as a precondition for knowledge management goals, (2) as a tool for knowledge management, and (3) as a condition for knowledge exchange. Critical thinking has been found to be one of the most important prerequisites for realising knowledge management goals.…”
Section: How Employers Encourage and Employees Experience Critical Thinkingsupporting
confidence: 91%
“…According to the employees, critical thinking is also strongly expressed in the context of information and knowledge management. This is in line with the results of a previous study (Indrašienė et al, 2021) emphasising that critical thinking can be interpreted in three ways: (1) as a precondition for knowledge management goals, (2) as a tool for knowledge management, and (3) as a condition for knowledge exchange. Critical thinking has been found to be one of the most important prerequisites for realising knowledge management goals.…”
Section: How Employers Encourage and Employees Experience Critical Thinkingsupporting
confidence: 91%
“…The finding partially supports who reported that knowledge sharing through social media promoted EFL teachers' reflectivity. In the same vein, the finding is in tandem with Indrašienė et al (2021) who studied the relationship between critical thinking and knowledge management and found a positive relationship between the two constructs. The study's findings can also be explained in the light of Vygotsky's (1978) were employed to improve higher-order thinking skills among university students.…”
Section: Discussionsupporting
confidence: 62%
“…In fact, the thinking itself needs knowledge as a core. That idea is supported by Indrasiene et al (2021) which stated that knowledge and critical thinking are related to one another. In this context, knowledge has a role as the content which forms critical thinking.…”
Section: Critical Thinking Knowledgementioning
confidence: 88%